Papillomas and carcinomas in transgenic rabbits carrying EJ-ras DNA and cottontail rabbit papillomavirus DNA. - Peng, X (1993)
Two transgenic rabbits (TRI and TRIII) that carried cottontail rabbit papillomavirus (CRPV) DNA alone were identified; another (TRII) carried both CRPV DNA and EJ-ras. TRI and TRIII developed extensive skin papillomas at about 1 month of age, and transcripts of CRPV DNA were detectable only in skin and/or papillomas. TRII developed extensive squamous carcinomas of the skin at a very early age. Transcription of both CRPV DNA and EJ-ras was found in the skin cancers. Thus, the tissue specificity of CRPV DNA expression in transgenic rabbits was the same as in virion-infected animals. The expression of EJ-ras could be dependent on the expression of certain CRPV genes and may be a critical cofactor of CRPV DNA in the progression of carcinomas.